1996
DOI: 10.1159/000227529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cisplatin on Cell Cycle Kinetics, Morphological Change, and Cleavage Pattern of DNA in Two Human Ovarian Carcinoma Cell Lines

Abstract: We evaluated the effects of cisplatin on the cell kinetics, cytomorphological changes, and cleavage patterns of DNA in two lines of human ovarian carcinoma cells. KF-1 cells displayed a cell cycle arrest in the G2M phase, while HMG cells displayed a transient cell accumulation in the S phase, without obvious G2M arrest. Morphological changes characterized by condensation and fragmentation of chromatin, and DNA cleavage by oligonucleosome-sized DNA fragments were observed in the HMG cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…Regarding the underlying mechanisms, Dimanche-Boitrel's [29] and Itamochi's groups [31] proposed that an increased number of resting (non-proliferating) cells may contribute to elevated chemoresistance at higher seeding densities. However, although our FCM analysis supports the hypothesis that dividing cells (G2-M phase) are major targets of cisplatin [3234], we could not verify that the cell cycle plays a central role in the density-dependent variation in IC 50 values (Figure 4B and 4C). Wu's group explained this phenomenon from the perspective of density-related apoptosis and autophagy [35].…”
Section: Discussioncontrasting
confidence: 81%
“…Regarding the underlying mechanisms, Dimanche-Boitrel's [29] and Itamochi's groups [31] proposed that an increased number of resting (non-proliferating) cells may contribute to elevated chemoresistance at higher seeding densities. However, although our FCM analysis supports the hypothesis that dividing cells (G2-M phase) are major targets of cisplatin [3234], we could not verify that the cell cycle plays a central role in the density-dependent variation in IC 50 values (Figure 4B and 4C). Wu's group explained this phenomenon from the perspective of density-related apoptosis and autophagy [35].…”
Section: Discussioncontrasting
confidence: 81%
“…Activation of p53 by cisplatin-induced DNA damage has been reported to have various effects on cellular sensitivity to cisplatin. In some studies, activation of p53 has been shown to provide cytoprotection against cisplatin [21], [22] In contrast, increased resistance to cisplatin with disruption of normal WT p53 function has also been demonstrated [23].…”
Section: Discussionmentioning
confidence: 99%
“…shown to arrest cell cycle in the G2 phase across a range of tumour types and it is the lack of progression across the G2/M transition which leads to apoptotic cell death 467,472,473 . The G2 arrest could be seen as the result of the formation of platinum adducts during the S phase of the cell cycle where DNA is replicated.…”
Section: ) Cisplatin Has Beenmentioning
confidence: 99%